Lignite in the Polish energy industry - a premature goodbye - Naworyta, Wojciech; Urbański, Paweł (Geologos, 2025)
Despite decarbonisation, coal (including lignite) still plays an important role in Europe in stabilising energy systems and guaranteeing energy security of many countries. The present article outlines the importance of lignite in Poland, the volume of extraction over several decades and its share in the production of electricity against the background of a changing energy structure. Due to the growing importance of renewable energy sources, lignite mining is declining year after year. However, during unfavourable periods for renewable energy sources, especially in winter, energy is produced primarily in conventional power plants. In 2023, over 21 per cent of Polish energy was generated from lignite. Therefore, first, lignite mining and electricity production are here characterised. Then, the short-term liquidation of existing mining and energy complexes is indicated, as a result of the exhaustion of lignite resources. Within two decades, 8.2 GW of lignite-based power will be lost from the Polish energy system. The geological resources of lignite deposits in Poland are described, paying particular attention to deposits whose extraction is possible and rational in the future. Finally, arguments are presented for maintaining lignite mining in Poland, as supported by the constantly growing demand for energy and the ability to flexible adjustment of electricity generation to variable production from renewable energy sources. Moreover, the possibility of minimising the environmental impact of both lignite mining and electricity generation from it need to be considered. Geopolitical events during the last decade, in particular the Russian aggression against Ukraine, have shown that domestic energy resources play an important role in ensuring the country’s energy security. Hence, the current study is an attempt to provide answers to the question whether it is not too early to say goodbye to Polish lignite.